PERBEDAAN ICHININSHO DAIMEISHI MENURUT GENDER - CUK YUANA (Universitas 17 Agustus 1945 Surabaya, 2018)
The variety of languages can be traced in every language. However from gender point view, it seems that every language does not have any differences. The different choice of vocabulary or goi used by men and women can be classified in Futsuu Meishi (noun), Ichininsho Daimeshi (first person pronoun), and Sanninsho Daimeishi (third person pronoun). This research focuses on futumeishi and Ichininsho Daimeishi. In futsumeishi, female speakers tend to add the prefix